An Exploration of Scientific Literacy on Physics Subjects within Phenomenon-based Experiential Learning - Santhalia, Prima Warta; Yuliati, Lia (Universitas Negeri Surabaya, 2021)
Scientific literacy is the ability to involve yourself in problems related to science. This research aims to explore the effect of phenomenon-based experiential learning on students' scientific literacy on expansion concept. This research was conducted with a mix-method approach with embedded experimental model design. The sample of this research was 32 students of grade 9 of a Senior High School in Malang, East Java, Indonesia. The data were collected through a scientific literacy tests (r = 0.53) and open-ended questions interviews to all the students, then be analyzed by using the Mann Whitney U-Test quantitatively and by using the Bybee (1997) assessment rubric qualitatively. Based on the results, it was found that the majority of students experienced an increase in their scientific literacy from the SI category (96.88%) into CSL (46.88). Future studies are expected to explore students' scientific literacy on other topics of physics education and utilize appropriate models in order to improve students' scientific literacy.